Learning Model Experiential-Based Environmental Socio-Scientific Issues (ESSI) and Their Effect on Critical and Creative Thinking Skills - Alpahmi Aji Satria; Sulistyo Saputro; Sutarno; Harjana; Fais Nurul Hadi (Jurnal Pendidikan IPA Indonesia, 2024)
In the midst of the accelerating pace of change in the modern world, critical and creative thinking skills are important for every individual, especially students.  Educators must understand their role in helping students develop critical and creative thinking skills. This study aims to apply the Experiential based Environmental Socio Scientific Issues learning (EBESSIL) model and test its effect on improving students' critical and creative thinking skills. The type of research was quasi-experimental with a pretest-posttest non-equivalent control group design. The research sample consisted of 70 students taken from SMA Negeri 1 Tiga Dihaji and SMA Negeri 1 Buay Sandang Aji class X South Sumatra. Data collection of students' critical and creative thinking skills using test instruments. The instrument was tested for construct validity using LISREL with Confirmatory Factor Analysis (CFA). Data analysis technique using MANOVA test. The results showed that the average value of students' critical and creative thinking skills in the experimental group was higher. The results of the MANOVA analysis showed that the learning model used had a significant effect on students' critical and creative thinking skills and was effective with a high category. The effect size value obtained d = 1.66 with a high category at a probability of excellence of 80%. Thus learning using the EBESSIL model is more effective and has a high influence on the ability of critical and creative thinking skills. From the results of this study, it can be concluded that the application of the EBESSIL learning model is more effective in improving students' critical and creative thinking skills. Researchers recommend that the EBESSIL learning model can be applied in high schools to help schools improve students' critical and creative thinking skills.